Latvian language as a code in different communication channels (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
This paper is dedicated to analyze of Latvian language as a code in such literary communication channels like press, poet, prose, legal literature. Calculations for zero-order, first-order, second-order and third-order Shannon entropy have been made and also corresponding values of redundancy and compression coefficients have been determined. All the calculations are done with a self-made computer program. Different communication channels of Latvian language are compared mutually and also Latvian language is compared with English and Russian as codes.